Pengembangan Modul Desain Didaktis Materi Statistika pada Pembelajaran Matematika di kelas VIII - Islamiyah, Tsuwaibatul; Mahmudah, Wilda (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
This research aims to develop a didactical design module for statistical material that is valid, practical, and effective. The type of research used is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The instruments used are questionnaires regarding students' initial needs, teacher interview sheets, validation sheets, student response questionnaires, and learning outcomes tests. The results of the research show that the didactic design module for statistical material is valid in terms of material validity, obtaining an average score of 4.22 with